Clinical and Genetic Investigations of 109 Index Patients With Dilated Cardiomyopathy and 445 of Their Relatives. (October 2020) - Hey, Thomas M.; Rasmussen, Torsten B.; Madsen, Trine; Aagaard, Mads Malik; Harbo, Maria; Mølgaard, Henning; Nielsen, Søren K.; Haas, Jan; Meder, Benjamin; Møller, Jacob E.; Eiskjær, Hans; Mogensen, Jens
Abstract : Background: It was the aim to investigate the frequency and genetic basis of dilated cardiomyopathy (DCM) among relatives of index patients with unexplained heart failure at a tertiary referral center. Methods: Clinical investigations were performed in 109 DCM index patients and 445 of their relatives. All index patients underwent genetic investigations of 76 disease-associated DCM genes. A family history of DCM occurred in 11% (n=12) while clinical investigations identified familial DCM in a total of 32% (n=35). One-fifth of all relatives (n=95) had DCM of whom 60% (n=57) had symptoms of heart failure at diagnosis, whereas 40% (n=38) were asymptomatic. Symptomatic relatives had a shorter event-free survival than asymptomatic DCM relatives ( P <0.001). Results: Genetic investigations identified 43 pathogenic (n=27) or likely pathogenic (n=16) variants according to the American College of Medical Genetics and Genomics and the Association for Molecular Pathology criteria. Forty-four percent (n=48/109) of index patients carried a pathogenic/likely pathogenic variant of whom 36% (n=27/74) had sporadic DCM, whereas 60% (21/35) were familial cases. Thirteen of the pathogenic/likely pathogenic variants were also present in ≥7 affected individuals and thereby considered to be of sufficient high confidence for use in predictive genetic testing. Conclusions: A family history of DCM identified only 34% (n=12/35) of hereditary DCM, whereas systematic clinical screening identified the remaining 66% (n=23) of DCM families. This emphasized the importance of clinical investigations to identify familial DCM. The high number of pathogenic/likely pathogenic variants identified in familial DCM provides a firm basis for offering genetic investigations in affected families. This should also be considered in sporadic cases since adequate family evaluation may not always be possible and the results of the genetic investigations may carry prognostic information with an impact on individual management. Abstract : Supplemental Digital Content is available in the text.